2012
DOI: 10.3354/ame01551
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of phototrophic, heterotrophic, and mixotrophic nanoflagellates in the microbial food web of a river-influenced coastal upwelling area

Abstract: . However, since HNF dominated in terms of abundance, they were the dominant grazers on bacterioplankton populations. Estimates of grazing pressure for the microbial food web showed that MNF were capable of removing 1 to 51% BP d . Given the area's relatively high nutrient condition, the elevated MNF biomass in the river plume and the greater bacterivory impact from MNF in winter, it seems that light and, thus, the energy/carbon limitation could be the main trigger for mixotrophy in this river-influenced coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
(66 reference statements)
3
10
0
Order By: Relevance
“…In spite of being a rough estimate, this provides indirect evidence for heterotrophy of PNF in a coastal upwelling system and delivers a value for carbon fraction acquired by heterotrophy similar to values reported in laboratory experiments (Sanders et al, 1990;Skovgaard et al, 2000). This estimated range of heterotrophy is also similar to levels provided by Vargas et al (2012) for an upwelling area off central Chile.…”
Section: Pigmented Nanoflagellates and Mixotrophic Nutrition In The Nsupporting
confidence: 79%
See 1 more Smart Citation
“…In spite of being a rough estimate, this provides indirect evidence for heterotrophy of PNF in a coastal upwelling system and delivers a value for carbon fraction acquired by heterotrophy similar to values reported in laboratory experiments (Sanders et al, 1990;Skovgaard et al, 2000). This estimated range of heterotrophy is also similar to levels provided by Vargas et al (2012) for an upwelling area off central Chile.…”
Section: Pigmented Nanoflagellates and Mixotrophic Nutrition In The Nsupporting
confidence: 79%
“…However, recent studies in some coastal upwelling systems have demonstrated that the group of pigmented flagellates 2-20 µm in size (PNF) is an important component of the microbial planktonic community, with its biomass exceeding that of diatoms when upwelling relaxes (e.g., Iriarte et al, 2000;Lorenzo et al, 2005;Böttjer and Morales, 2007). As mixotrophy in this plankton group has been described on only one occasion for coastal upwelling systems (Vargas et al, 2012), there is an urgent need to know the occurrence and magnitude of this type of nutrition in PNF to better understand the flows of matter and energy in these productive coastal waters.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we suggest that mixotrophy of large plastidic protists, that is, preying on methylotrophic bacteria could have been occurring. Mixotrophy in natural populations of nano-plankton has been previously documented in other coastal upwelling regions, for example, North West Iberian upwelling system (Crespo et al, 2011;Vargas et al, 2011;Hartmann et al, 2012 and references therein) and in both temperate and oligotrophic regions of the Atlantic ocean (Zubkov and Tarran, 2008;Hartmann et al, 2012). Alternatively, the correlation found in Mauritanian upwelling waters between microbial methanol assimilation and primary productivity could be an indirect effect, of possibly a distinct group of methylotrophs associated with upwelling waters that uniquely use up to 57% of the methanol for cellular incorporation.…”
Section: Discussionmentioning
confidence: 99%
“…SANCHÉZ et al, 2011;VARGAS et al, 2012). Nevertheless, the present study reveals the complexity of the plankton structure in systems with high hydrological variability and represents an important starting point for the modelling of the carbon fluxes in this and other similar tropical systems.…”
Section: Trophic Interactionsmentioning
confidence: 97%